1999
DOI: 10.1523/jneurosci.19-18-07711.1999
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Expression of Neural Nitric Oxide Synthase (nNOS) Protein Is Suppressed by an Antisense RNA Transcribed from an NOS Pseudogene

Abstract: Here, we show that a nitric oxide synthase (NOS) pseudogene is expressed in the CNS of the snail Lymnaea stagnalis. The pseudo-NOS transcript includes a region of significant antisense homology to a previously reported neuronal NOS (nNOS)-encoding mRNA. This suggested that the pseudo-NOS transcript acts as a natural antisense regulator of nNOS protein synthesis. In support of this, we show that both the nNOS-encoding and the pseudo-NOS transcripts are coexpressed in giant identified neurons (the cerebral giant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
209
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(214 citation statements)
references
References 31 publications
2
209
0
3
Order By: Relevance
“…Transcription of a pseudogene that is homologous to the neuronal nitric oxide synthase (nNOS) gene in a population of neurons decreases the expression levels for the nNOS gene. Interestingly, RNA isolated from these neuronal cells confirmed the presence of an in vivo stable RNA-RNA duplex between these two transcripts suggested to arise via a reversecomplement sequence found at the 5Ј end of the pseudo-NOS transcript (Korneev et al 1999). This study implicated the pseudo-NOS transcript as a natural antisense regulator of nNOS protein synthesis (Korneev et al 1999).…”
Section: Pseudogene Transcripts: No More 'Junk'mentioning
confidence: 68%
See 1 more Smart Citation
“…Transcription of a pseudogene that is homologous to the neuronal nitric oxide synthase (nNOS) gene in a population of neurons decreases the expression levels for the nNOS gene. Interestingly, RNA isolated from these neuronal cells confirmed the presence of an in vivo stable RNA-RNA duplex between these two transcripts suggested to arise via a reversecomplement sequence found at the 5Ј end of the pseudo-NOS transcript (Korneev et al 1999). This study implicated the pseudo-NOS transcript as a natural antisense regulator of nNOS protein synthesis (Korneev et al 1999).…”
Section: Pseudogene Transcripts: No More 'Junk'mentioning
confidence: 68%
“…A role of pseudogene transcripts in gene regulation has also been reported in the snail Lymnea stagnalis (Korneev et al 1999(Korneev et al , 2005. Transcription of a pseudogene that is homologous to the neuronal nitric oxide synthase (nNOS) gene in a population of neurons decreases the expression levels for the nNOS gene.…”
Section: Pseudogene Transcripts: No More 'Junk'mentioning
confidence: 98%
“…Although the process of retrotransposition may have been necessary for genome evolution (36), the vast majority of existing pseudogenes are considered as ''junk'' DNA. Although some are transcribed, many have accumulated mutations that would preclude function, and only a very small number may play physiological roles (37)(38)(39). Indeed, even though exon shuffling may have been of great importance in the evolutionary past (40,41), the Trim5-CypA protein appears to belong to a tiny handful of functional proteins unambiguously created in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…PCR ampliWcation of products longer than 4.5 kb were ampliWed with the Expand High Fidelity system (ROCHE), using ampliWcation programs as indicated in the manufacturer's instructions. Doublestranded RNA was detected according to the protocol described in Korneev (1999). The list of the primers used in this study is found in supplementary Materials and methods, Table 1.…”
Section: Genome Walkmentioning
confidence: 99%
“…The smear at the bottom of the Southern blot is likely due to breakdown of the radioactively labelled Wrst strand during PCR and/or linear ampliWcation of breakdown products which have lost one primer-annealing site, but which still can hybridise to the radioactive probe Parts of RSI RNA and the TNP RNA form double-stranded RNA The detection of the RSI-ATs suggested that doublestranded RNAs (dsRNA) might form in cells where both RSI and RSI-ATs transcripts are expressed. To detect dsRNA we took advantage of the methods described in Korneev et al (1999), which exploited the feature of the RNase-ONE enzyme to degrade single-stranded RNA leaving dsRNA intact. Total RNA was extracted under non-denaturing conditions, treated with an excess of RNase-ONE and reverse-transcribed with primers located outside and inside the hypothetical dsRNA molecules (Fig.…”
Section: Fig 3 Detection Of Tamrsi-2 Transposition (A B) and Three mentioning
confidence: 99%